STRUCTURE ELUCIDATION OF ANTIBACTERIAL COMPOUND FROM Ficus deltoidea Jack LEAVES - Suryati Suryati; Hazli Nurdin; Dachriyanus Dachriyanus; Md Nordin Hj Lajis (Universitas Gadjah Mada, 2011)
An antibacterial compound has been isolated from Ficus deltoidea Jack leaves. Based on spectroscopic data (IR, 1H-NMR, 13C NMR 1D and 2D and MS), the structure of this compound was identified as 3β-hydroksilup-20(29)-en, (lupeol), C30H50O. This compound showed antibacterial activities against E. coli, B. subtilis and S. aureus. The minimum inhibition concentration (MIC) against E. coli, B. subtilis and S. aureus are 150, 220 and 130 μg/mL respectively.